EFEK EKSTRAK ETANOL DAUN SINGKONG (Manihot Utilissima Pohl) SEBAGAI OBAT ALTERNATIF ANTI REMATIK TERHADAP RASA SAKIT PADA MENCIT - Setya Enti Rikomah; Elmitra Elmitra; Diana Gustina Yunita (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Medicinal plants used for generations one of which is crop cassava leaves. Cassava leaves is believed to cure rheumatism, gout, anemia, constipation, and to increase endurance. This study aims to determine the Effects Of Ethanol Leaf Extract Singkong (Manihot Utilissima Pohl) As Drug Alternatif Antirheumatic Of Pain On Mice. This study was an experimental study using 25 mice. These animals were divided into five groups where each group consisted of 5 mice. Cassava leaf extracts as a control test, flamar gel as a positive control, and distilled water as a negative control. Observations were made for 45 minutes using a hot excitatory response in the form of a decrease in a lick or jump after the treatments. The results showed a decline in the response of mice to lick the feet or jump to the heat stimuli were administered after administration of cassava leaf extract. Cassava leaf extract has an effect antirheumatic to pain in mice. Based on the analysis of SPSS best dose in this study is the first dose (0.65mg / 20gr mice BB).